(untitled) (Scientific journal of the Fergana State University, 2024)
The article examines the impact of the placement of the population of the Republic of Karakalpakstan on the territorial organization of services to the population. The population size and its dynamics, differentiation of fertility, mortality, natural reproduction and migration processes across the administrative-territorial units of Karakalpakstan are considered.